Damage control surgery in weightlessness: A comparative study of simulated torso hemorrhage control comparing terrestrial and weightless conditions. Issue 2 (February 2017) - Kirkpatrick, Andrew W.; McKee, Jessica Lynn; Tien, Homer; LaPorta, Anthony J.; Lavell, Kit; Leslie, Tim; King, David R.; McBeth, Paul B.; Brien, Susan; Roberts, Derek J.; Franciose, Reginald; Wong, Jonathan; et al.
Abstract : BACKGROUND: Torso bleeding remains the most preventable cause of post-traumatic death worldwide. Remote damage control resuscitation (RDCR) endeavours to rescue the most catastrophically injured, but has not focused on prehospital surgical torso hemorrhage control (HC). We examined the logistics and metrics of intraperitoneal packing in weightlessness in Parabolic flight (0g) compared to terrestrial gravity (1g) as an extreme example of surgical RDCR. METHODS: A surgical simulator was customized with high-fidelity intraperitoneal anatomy, a "blood" pump and flowmeter. A standardized HC task was to explore the simulator, identify "bleeding" from a previously unknown liver injury perfused at 80 mm Hg, and pack to gain hemostasis. Ten surgeons performed RDCR laparotomies onboard a research aircraft, first in 1g followed by 0g. The standardized laparotomy was sectioned into 20-second segments to conduct and facilitate parabolic flight comparisons, with "blood" pumped only during these time segments. A maximum of 12 segments permitted for each laparotomy. RESULTS: All 10 surgeons successfully performed HC in both 1g and 0g. There was no difference in blood loss between 1g and 0g ( p = 0.161) or during observation following HC ( p = 0.944). Compared to 1g, identification of bleeding in 0g incurred less "blood" loss ( p = 0.032). Overall surgeons rated their personal performance and relative difficulty of surgery in 0g as "harder" (median Likert, 2/5). However, conducting all phases of HC were rated equivalent between 1g and 0g (median Likert, 3/5), except for instrument control (rated slightly harder, 2.75/5). CONCLUSION: Performing laparotomies with packing of a simulated torso hemorrhage in a high-fidelity surgical simulator was feasible onboard a research aircraft in both normal and weightless conditions. Despite being subjectively "harder, " most phases of operative intervention were rated equivalently, with no statistical difference in "blood" loss in weightlessness. Direct operative control of torso hemorrhage is theoretically possible in extreme environments if logistics are provided. Abstract : Supplemental digital content is available in the text.